Sponges and Sponge-Like Materials in Sample Preparation: A Journey from Past to Present and into the Future - Theodoros G. Chatzimitakos; Constantine D. Stalikas (Molecules, 2020)
Even though instrumental advancements are constantly being made in analytical chemistry, sample preparation is still considered the bottleneck of analytical methods. To this end, researchers are developing new sorbent materials to improve and replace existing ones, with the ultimate goal to improve current methods and make them more efficient and effective. A few years ago, an alternative trend was started toward sample preparation: the use of sponge or sponge-like materials. These materials possess favorable characteristics, such as negligible weight, open-hole structure, high surface area, and variable surface chemistry. Although their use seemed promising, this trend soon reversed, due to either the increasing use of nanomaterials in sample preparation or the limited scope of the first materials. Currently, with the development of new materials, such as melamine sponges, along with the advancement in nanotechnology, this topic was revived, and various functionalizations were carried out on such materials. The new materials are used as sorbents in sample preparation in analytical chemistry. This review explores the development of such materials, from the past to the present and into the future, as well as their use in analytical chemistry.